2013
DOI: 10.1177/0267659113513920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coronary artery bypass surgery on left ventricular function as assessed by strain and strain rate imaging

Abstract: The results of this study suggest that strain and strain rate echocardiography can provide an accurate evaluation of regional contractile function after CABG, even in the segments that are apparently normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…In a small study [9] of 25 children (age 9.4 ± 9.8 years), evaluating 3D LV ventricular strain at 1 week and 1 month after cardiac surgery for CHD, no significant differences in regional deformation were noted, except for a more pronounced reduction in strain values in the LV-free wall middle segments for cyanotic patients (p = 0.037). Curiously, the trend in postoperative apical hypercontractility we described herein is opposite to the one previously reported in adult [25,26] patients. In 182 patients, following different types of cardiac surgery (e.g., aortic valve replacement, mitral valve repair or replacement, coronary artery bypass graft), segmental function evaluated by 3D strain was greatly impaired in apical when compared to basal segments.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a small study [9] of 25 children (age 9.4 ± 9.8 years), evaluating 3D LV ventricular strain at 1 week and 1 month after cardiac surgery for CHD, no significant differences in regional deformation were noted, except for a more pronounced reduction in strain values in the LV-free wall middle segments for cyanotic patients (p = 0.037). Curiously, the trend in postoperative apical hypercontractility we described herein is opposite to the one previously reported in adult [25,26] patients. In 182 patients, following different types of cardiac surgery (e.g., aortic valve replacement, mitral valve repair or replacement, coronary artery bypass graft), segmental function evaluated by 3D strain was greatly impaired in apical when compared to basal segments.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study [25], however, many patients had left anterior descending coronary artery disease; thus, the differences in regional strain may be attributed to pre-existing coronary artery disease. The basal and middle segment strain values, in fact, seem to be ameliorated after coronary artery bypass surgery due to revascularization [25,26]. Thus, a comparison of adult data with those of children who usually have a normal coronary artery bed is difficult and should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…In the entire cohort, there was a significant improvement in global LV strain after CABG ( p = 0.03). This supports the findings of Yin et al [ 6 ] and Durmaz et al [ 20 ] who showed an improvement in the longitudinal deformation in patients with preserved LVEF after CABG. We believe that this finding is of exceptional clinical importance for two reasons: first, it confirms the success of myocardial revascularization and confirms the “awakening” of the subtly hibernating segments of the myocardium.…”
Section: Discussionsupporting
confidence: 92%